Casticin induces apoptosis and G0/G1 cell cycle arrest in gallbladder cancer cells. Issue 1 (December 2017) - Song, Xiao-ling; Zhang, Yun-jiao; Wang, Xue-feng; Zhang, Wen-jie; Wang, Zheng; Zhang, Fei; Zhang, Yi-jian; Lu, Jian-hua; Mei, Jia-wei; Hu, Yun-ping; Chen, Lei; Li, Huai-feng; et al.
Abstract Background Casticin, the flavonoid extracted fromVitex rotundifolia L, exerts various biological effects, including anti-inflammatory and anti-cancer activity. The aim of this study is to investigate the effects and mechanisms of casticin in human gallbladder cancer cells. Methods Human NOZ and SGC996 cells were used to perform the experiments. CCK-8 assay and colony formation assay were performed to evaluate cell viability. Cell cycle analyses and annexin V/PI staining assay for apoptosis were measured using flow cytometry. Western blot analysis was used to evaluate the changes in protein expression, and the effect of casticin treatment in vivo was experimented with xenografted tumors. Results In this study, we found that casticin significantly inhibited gallbladder cancer cell proliferation in a dose- and time-dependent manner. Casticin also induced G0/G1 arrest and mitochondrial-related apoptosis by upregulating Bax, cleaved caspase-3, cleaved caspase-9 and cleaved poly ADP-ribose polymerase expression, and by downregulating Bcl-2 expression. Moreover, casticin induced cycle arrest and apoptosis by upregulating p27 and downregulating cyclinD1/cyclin-dependent kinase4 and phosphorylated protein kinase B. In vivo, casticin inhibited tumor growth. Conclusion Casticin induces G0/G1 arrest and apoptosis in gallbladder cancer, suggesting that casticin might represent a novel and effective agent against gallbladder cancer.